Die kationische Caprolactam-Polymerisation - M. Rothe; G. Bertalan; J. Mazánek (CHIMIA)
The lactam polymerizations initiated by proton acids, Lewis acids, and ammonium salts, resp., as well as the hydrolytic polymerization are summarized as “cationic polymerizations”. Initiation and propagation reactions are due to the high acylating properties of the lactam cation which reacts with the strongest nucleophihc compound in the polymerization mixture.